2018
DOI: 10.1039/c8cs00431e
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot-sensitized solar cells

Abstract: Quantum dot-sensitized solar cells (QDSCs) have emerged as a promising candidate for next-generation solar cells due to the distinct optoelectronic features of quantum dot (QD) light-harvesting materials, such as high light, thermal, and moisture stability, facilely tunable absorption range, high absorption coefficient, multiple exciton generation possibility, and solution processability as well as their facile fabrication and low-cost availability. In recent years, we have witnessed a dramatic boost in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
234
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 371 publications
(238 citation statements)
references
References 492 publications
2
234
0
2
Order By: Relevance
“…[1,2] In recent years, there are many studies [3][4][5][6][7][8] focusing on energy storage and conversion setups to develop the method of collecting and using the renewable, sustainable, and green energy resource. [1,2] In recent years, there are many studies [3][4][5][6][7][8] focusing on energy storage and conversion setups to develop the method of collecting and using the renewable, sustainable, and green energy resource.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In recent years, there are many studies [3][4][5][6][7][8] focusing on energy storage and conversion setups to develop the method of collecting and using the renewable, sustainable, and green energy resource. [1,2] In recent years, there are many studies [3][4][5][6][7][8] focusing on energy storage and conversion setups to develop the method of collecting and using the renewable, sustainable, and green energy resource.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In the past few years, the power conversion efficiency (PCE) of liquid-junction QDSCs has been improved from less than 5% to over 12%, [5][6][7][8] which is still below with those of the emerging inorganic photovoltaic technologies such as perovskite CsPbI 3 QD-based solar cells. [1][2][3][4] In the past few years, the power conversion efficiency (PCE) of liquid-junction QDSCs has been improved from less than 5% to over 12%, [5][6][7][8] which is still below with those of the emerging inorganic photovoltaic technologies such as perovskite CsPbI 3 QD-based solar cells.…”
Section: Doi: 101002/adma201903696mentioning
confidence: 99%
“…The obtained Zn/Ti, Cu/Ti, and In/Ti atomic ratios for the cosensitized TiO 2 films were found to be higher than those for the single QD-based ones. [1] It has been demonstrated that the improved coverage of QDs on TiO 2 can better block the electron leakage from TiO 2 to electrolyte, reducing charge recombination loss. Generally, the increase in the QD loading amount on TiO 2 will help to suppress the interfacial charge recombination process.…”
Section: Doi: 101002/adma201903696mentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, semiconductor quantum dots (QDs) have been intensively studied due to their appealing optical properties such as high color purity, emission peak tunability, high brightness and photostability . They have promising applications in solar cell, light emitting diodes (LEDs), sensors, fluorescent probes, biolabeling, and anticounterfeiting . For example, QDs‐based LEDs, so called QLEDs, exhibit longer photoluminescence (PL) lifetime and higher thermal stability than organic light emitting diodes and, therefore, have been applied in the latest generation of displays .…”
Section: Introductionmentioning
confidence: 99%